Konsepsi Hukum Negara Nusantara pada Konferensi Hukum Laut Ke-III - Kusumaatmadja, Mochtar (UI Scholars Hub, 2021)
Indonesia as one of the countries, which is trying to struggle for archipelagic State conception to be accept in universal scope after bilateral and regional lobbies. Archipelagic State conception has already existed since nineteen twentieth and Indonesia wants to make this conception being a part of positive law of international law of the Sea. Prof. Mochtar Kusumaatmadja as a leader of the Indonesian delegation to the Third United Nations Conference on the Law of the Sea in Caracas, make this paper to describe Indonesia and other countries effort in the Conference to put the law status of archipelagic State into a convention about International Law of the Sea.